Parents' Coping Strategies in Caring for Children with Special Needs: A Narrative Review - Ikeu Nurhidayah; Meisha Nurlianti Hidayat; Titin Sutini (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The presence of children with special needs (CSN) causes anxiety in parents who are responsible for their children. Individuals who are stressed are stimulated to do something in response to the stress, which is referred to as coping. Parents of children with special needs employ a variety of coping strategies, depending on the nature of the issues they face. The purpose of this study was to identify parents' coping mechanisms while dealing with children with special needs. A narrative review is a method of conducting a literature review. The keywords coping methods / coping behavior, parents, and special needs children / disabled children were searched in the online databases EBSCOhost, PubMed, and Google Scholar. The search yielded 25 publications that were found to be related to the study's goals. According to the findings of this literature review, parents utilize problem-focused and emotional-focused coping when caring for their children with special needs. When it comes to caring for children with special needs, parents employ a variety of coping mechanisms. The employment of parental coping mechanisms varies from one article to the next. As a result, more comprehensive research on aspects associated to parental coping techniques in managing children with special needs is required. Nurses can help parents deal with stress while caring for children with special needs by acting as educators, counselors, advocates, and collaborators with other health professionals.Abstrak: Kehadiran anak berkebutuhan khusus (ABK) memicu stres orang tua dalam merawat anaknya. Stres yang dirasakan individu menstimulus individu untuk melakukan sesuatu dalam menghadapi stres,yang dinamakan dengan koping.Orang tua dengan ABK menggunakan perilaku koping yang berbeda-beda tergantung pemaknaan masalah yang dihadapinya. Tujuan penelitian ini yaitu untuk mensintesis penelitian yang telah ada mengenai strategi koping yang digunakan orang tua dalam merawat ABK. Metode studi literatur ini adalah narrative review. Basis data daring yang digunakan yaitu EBSCOhost, PubMed, dan Google Scholar, dengan kata kunci coping strategies / coping behaviour, parents, dan special needs children / disabled children. Hasil pencarian didapatkan 25 artikel yang teridentifikasi dan relevan dengan tujuan penelitian. Hasil studi literatur ini menunjukkan bahwa koping yang digunakan oleh orang tua dalam merawat ABK adalah koping berfokus pada masalah dan koping berfokus pada emosi. Terdapat berbagai jenis strategi koping yang digunakan orang tua dalam merawat ABK. Masing-masing artikel menunjukkan perbedaan penggunaan strategi koping orang tua. Maka dari itu, perlu dilakukan penelitian lebih lanjut secara komprehensif mengenai faktor yang berhubungan dengan strategi koping orang tua dalam merawat ABK. Perawat dapat berperan sebagai edukator, konselor, advokator, dan kolaborator dengan profesional kesehatan lain untuk memfasilitasi orang tua dalam mengatasi stres selama merawat ABK.